Comprensión lectora y logros de aprendizaje en el área de ciencias sociales de los estudiantes de VII ciclo de la Institución Educativa Elzeario Mac Donald, Pebas 2023 - Nolorbe Luque, Nixon (2025)
The general objective of this research was to determine the relationship between reading comprehension and learning achievement in the area of social sciences among students in the seventh cycle of the Elzeario Mac Donald Educational Institution, Pebas, 2023. The research was descriptive and correlational. The population consisted of 260 students from the Elzeario Mac Donald Educational Institution. From this, a sample of 165 secondary education students from the seventh cycle of the Elzeario Mac Donald Educational Institution, located in the district of Pebas, Ramón Castilla province, was drawn in 2023. The sample was selected based on a sample design for populations under 1,500. The data collection instrument used was a survey, the purpose of which was to study the relationship between reading comprehension and learning achievement in the area of social sciences. The most important results are: 50.3% of students have an average reading comprehension level. This indicates that the majority of students have average reading comprehension, while a significant percentage still have difficulties with reading comprehension. Regarding learning achievement, the majority of students (46.1%) are at the "In Progress" level, suggesting that most students need additional support to achieve higher performance. It can be concluded that better reading comprehension is associated with higher achievement in Social Studies, although only a small percentage of students with high comprehension excel. The distribution indicates that, in general, students with higher reading comprehension achieve better performance in the subject.